Bài 1 tính
\(\frac{X^2-36}{2X+10}.\frac{3}{6-X}\)
\(\frac{X^2-4}{X^2-9}.\frac{3X+9}{X+2}\)
\(\frac{X^3-8}{5X+20}.\frac{X^2+4X}{X^2+2X+4}\)
\(\frac{4X+12}{\left(X+4\right)^2}:\frac{3X+9}{X+4}\)
\(\frac{5X-10}{X^2+7}:2X+4\)
\(X^2-25:\frac{2X+10}{3X-7}\)
\(\frac{x^2-36}{2x+10}\cdot\frac{3}{6-x}=\frac{\left(x-6\right)\left(x+6\right)}{2x+10}\cdot\frac{3}{6-x}=-\frac{3\left(x+6\right)}{2x+10}=-\frac{3x+18}{2x+10}\)
\(\frac{x^2-4}{x^2-9}\cdot\frac{3x+9}{x+2}=\frac{\left(x-2\right)\left(x+2\right)}{\left(x+3\right)\left(x-3\right)}\cdot\frac{3\left(x+3\right)}{x+2}=\frac{3\left(x-2\right)}{x-3}\)
\(\frac{x^3-8}{5x+20}\cdot\frac{x^2+4x}{x^2+2x+4}=\frac{\left(x-2\right)\left(x^2+2x+4\right)}{5\left(x+4\right)}\cdot\frac{x\left(x+4\right)}{x^2+2x+4}=\frac{x\left(x-2\right)}{5}\)
\(\frac{4x+12}{\left(x+4\right)^2}:\frac{3x+9}{x+4}=\frac{4\left(x+3\right)}{\left(x+4\right)^2}\cdot\frac{x+4}{3\left(x+3\right)}=\frac{4}{3\left(x+4\right)}\)